EFEKTIVITAS BAHAN AJAR BAHASA INDONESIA BERBASIS MULTIMEDIA INTERAKTIF PADA PESERTA DIDIK KELAS IV - Fitri Wahyuni; Munirah Munirah; Sulfasyah Sulfasyah (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE EFFECTIVENESS OF INTERACTIVE MULTIMEDIA-BASED INDONESIAN TEACHING MATERIALS FOR CLASS IV STUDENTSThis study aims to determine the effectiveness of interactive multimedia-based Indonesian language teaching materials for fourth grade students of SD Inpres Pallangga, Tinggimoncong District, Gowa Regency. This type of research used in this research is experimental research. In this experimental study, researchers used a Pre-Experimental Desing (Nondesings) design using the One-Group Pretest-Posttest design. The subjects in this study were students in grade IV. Instruments Data collection was carried out through observation sheets, test sheets in the form of pretest and posttest, and instruments for student learning outcomes. The data analysis technique used was descriptive data analysis. The results showed that the interactive multimedia-based Indonesian language teaching materials in the form of interactive multimedia-based Indonesian language teaching materials from the results of the research were declared effective because the average learning outcomes of students reached 88% completeness in the very good category, students were very active and liked teaching materials. which is presented and makes it easy for the teacher to deliver the material.